2017
DOI: 10.1007/s00466-017-1438-8
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modeling of quasi-brittle cracks in 2D and 3D with enhanced strain accuracy

Abstract: The final publication is available at Springer via http://dx.doi.org/10.1007/s00466-017-1438-8This paper discusses the finite element modeling of cracking in quasi-brittle materials. The problem is addressed via a mixed strain/displacement finite element formulation and an isotropic damage constitutive model. The proposed mixed formulation is fully general and is applied in 2D and 3D. Also, it is independent of the specific finite element discretization considered; it can be equally used with triangles/tetrahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 74 publications
(139 reference statements)
2
23
0
Order By: Relevance
“…It is found that the crack initially twists along the central vertical axis until the crack surface is parallel to the transversal plane, and then grows upwards along the transversal plane until the end of simulations. The simulated crack surface represented by points ( d > 0.9) is visualized in Figure 15 where the crack propagation patterns are in good agreement with reference solutions 36,53,54 . Figure 16 shows the load‐displacement curve for a three‐point bending test.…”
Section: Numerical Examplesmentioning
confidence: 59%
“…It is found that the crack initially twists along the central vertical axis until the crack surface is parallel to the transversal plane, and then grows upwards along the transversal plane until the end of simulations. The simulated crack surface represented by points ( d > 0.9) is visualized in Figure 15 where the crack propagation patterns are in good agreement with reference solutions 36,53,54 . Figure 16 shows the load‐displacement curve for a three‐point bending test.…”
Section: Numerical Examplesmentioning
confidence: 59%
“…These observations are in agreement with the work of Cervera et al Indeed, they mention that in order to obtain crack paths and failure strains independent of the discretization, one needs to have both a smooth strain field and a fracture criterion function of the discretization length. TLSPH provides a smooth strain field, but the fracture criterion used here is independent of the particle spacing.…”
Section: Convergencementioning
confidence: 99%
“…Finally, a three-point bending test on skew notched beam has been performed. The FEM-DEM results have been compared with those obtained by Cervera et al [47]. For the 2D examples (Section 6.1) we have used 3-noded triangles.…”
Section: Numerical Examplesmentioning
confidence: 99%